2005
DOI: 10.1093/ndt/gfh739
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tacrolimus compared with cyclosporin A microemulsion in renal transplantation: 2 year follow-up results

Abstract: The 2 year study results confirm that tacrolimus is a highly efficacious cornerstone immunosuppressant in kidney transplantation. Tacrolimus-based immunosuppression may induce long-term benefits with regard to graft function and graft survival. The overall side-effect profile is considered to be favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 18 publications
2
77
2
8
Order By: Relevance
“…The study confirmed that patients treated with tacrolimus have better cardiovascular risk profiles compared with cyclosporine-treated patients (30,31,32). Cyclosporine patients in our study had higher cholesterols and systolic BP, as expected.…”
Section: Discussionsupporting
confidence: 89%
“…The study confirmed that patients treated with tacrolimus have better cardiovascular risk profiles compared with cyclosporine-treated patients (30,31,32). Cyclosporine patients in our study had higher cholesterols and systolic BP, as expected.…”
Section: Discussionsupporting
confidence: 89%
“…Newer maintenance immunosuppressive regimes, featuring tacrolimus and mycophenolate mofetil, have reduced the acute rejection rate; however, their effect on long-term graft outcome is not without debate. [2][3][4][5][6][7] One-year graft survival rates in our cohort of patients have improved from 82% to 86% in the period 1986-2001. [8] Irish Renal Transplant Registry data indicate that our acute rejection rate has improved from 30% in the 1990s to less than 10% currently.…”
Section: Introductionmentioning
confidence: 99%
“…Graft loss, patient death and biopsy-proven acute rejection occurred signifi cantly more frequently in patients treated with cyclosporin than in the tacrolimus arm. Graft function at 2 years post-transplantation was signifi cantly better and cholesterol and triglycerides concentrations were lower in the tacrolimus arm compared to the cyclosporine arm 21 . In the European Switch to Tacrolimus Study 296 adult kidney transplant patients with cyclosporine related side eff ects were converted to tacrolimus.…”
Section: Discussionmentioning
confidence: 96%